The established and the challenger: a direct comparison of current cryoballoon technologies for pulmonary vein isolation - Moser, Fabian (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2022)
Introduction: Cryoballoon ablation for pulmonary vein isolation is an effective treatment of atrial fibrillation (AF). Recently, a novel cryoablation system was introduced. The aim of the study was to compare the safety, efficacy and biophysical characteristics of a novel cryoablation system (POLARxTM, Boston Scientific) to a commonly used and clinically well characterized system (Arctic Front Advance ProTM, AFA, Medtronic). Methods and Results: Fifty consecutive patients with symptomatic AF, who underwent cryoballoon-based ablation with the POLARx were compared to 50 consecutive patients treated with the AFA. Acute pulmonary vein isolation was achieved in 99.8% (POLARx 99.5%, AFA 100%, p=1.00). Time to isolation (TTI) was comparable in both groups (POLARx 35 [27, 48] sec, AFA 30 [21, 43] sec, p=0.165). The POLARx showed a lower balloon temperature at TTI (POLARx -44 [-50, -36] °C, AFA -31 [-38, -21] °C, p<0.001) and lower nadir temperature (POLARx -60 [-65, -55] °C, AFA -48 [-54, -45] °C, p<0.001). Procedure time (POLARx 80 [60, 105] min, AFA 62 [42, 80] min, p<0.001), fluoroscopy time (POLARx 17 [13, 22] min, AFA 11 [7, 16] min, p<0.001) and freeze cycles per patient (POLARx 5 [4, 6], AFA 4.5 [4, 5], p=0.002) were higher in the POLARx group. Two cerebral ischemic events occurred in the POLARx group, two patients in each group had phrenic nerve injury. Conclusion: Both systems enable effective isolation of pulmonary veins. The POLARx required longer procedure and fluoroscopy times. Larger, prospective and randomized studies are needed to assess long-term efficacy and safety of this technology.